'A community development yet-to-come': Jacques Derrida and re-constructing community development praxis. (19th June 2019) - Westoby, Peter
Abstract: This chapter provides a concise overview of the life and career of Jacques Derrida, exploring how his substantive philosophical writing could be relevant to a community development 'yet-to-come' and specifically for a renewed praxis. Derrida was a leading intellectual of what is commonly known as deconstruction, and while never explicitly writing to community development, his later work became more overtly political, hence a relevance. Following a biographical sketch, the 'traces' of some key elements of his work outlined foregrounding three key threads, all equally important, all interlinked. The provocation of this article is that without a radical re-constituting of praxis– a deconstructive task – community development is at risk of ossifying into a programme that is no longer haunted by justice, is no longer mobilized by the 'passion-of-not-knowing' and is no longer vigilant towards the Other.